Click farm platforms: An updating of informal work in Brazil and Colombia. (17th October 2022) - Grohmann, Rafael; Clara Aquino, Maria; Rodrigues, Alison; Matos, Évilin; Govari, Caroline; Amaral, Adriana
Abstract : The article analyses work on click farm platforms in Brazil and Colombia. It argues that work on these platforms updates and renews the historical informality of work in Latin America. Drawing on click farm ethnography, worker interviews and digital ethnography on WhatsApp and Facebook groups and Youtube channels, the research highlights: first, the cultural marks of Brazil and Colombia in the interactions between workers, typical of Latin American digital culture; second, the role of Youtubers as skill makers, responsible for the initiation of workers into click farm platforms and the circulation of neoliberal and entrepreneurial ideology; third, practices and discourses relating to reselling accounts, photos and bots as a new version of the historical resale markets in the region; and fourth, the boundaries between informality and illegality at work on click farm platforms. The article argues that, in addition to informal work that preceded and is connected to work on click farms, informality gains new dimensions with work on click farms, with the platformisation of labour representing an articulation between the old informality and new market practices and infrastructures.